Exploring the concept of agroecological food systems in a city-region context - Vaarst, Mette; Escudero, Arthur Getz; Chappell, M. Jahi; Brinkley, Catherine; Nijbroek, Ravic P.; Arraes, Nilson A.M.; Andreasen, Lise; Gattinger, Andreas; Fonseca De Almeida, Gustavo; Bossio, Deborah A.; Halbergh, Niels (Informa UK Limited, 2018)
Based on urgent needs for food security compounded by a changing climate which impacts and is impacted by agricultural land-use and food distribution practices, we explore the processes of action in implementing agroecological food systems. We identified the following characteristics for an agroecological food system: 1. Minimizing use of external inputs, 2. Extent of internal resource recycling, 3. Resilience, 4. Multifunctionality, 5. Building on complexity and incorporating greater systems integration, 6. Contextuality, 7. Equity and, 8. Nourishment. We focus on the city-region food systems context, concluding with practical drivers for realizing more agroecological food systems in city-region contexts. Agroecological food systems are widely diverse, shaped by context, and achieved through multi-actor planning in rural, peri-urban and urban areas. Application of agroecological food systems in rural–urban contexts emphasize the necessity of diversification, zoning rural–urban landscapes, planning for seasonality in a food systems context, and producing at scale. Rural–urban food systems are a relevant and challenging entry point that provides opportunities for learning how food systems can be shaped for significant positive change. Social organization, community building, common learning, and knowledge creation are crucial for agroecological contextualized food systems, as are the supports from appropriate governing and institutional structures.